A Feasibility Study on HIT Enterprises - Herrin, Mark Andrew C. (College of Engineering, 2003)
Hamper Innovation Technologies, Inc. is a plastic manufacturing company that specializes in the innovation of laundry hampers. HIT Enterprises, Inc. strives to bring the most innovative laundry hampers of exceptional quality to the Filipino people. This study documents the operations, facilities, requirements and organizational structure needed for the company to operate and will test if feasibility in four different fields, namely Marketing, Technical, Financial and Socio-Profitability. In the marketing study, the main instrument used was a survey that contained pertinent questions regarding such a product and was directed towards the target market. Supply and demand information was acquired, and the potential market share capturable by HIT Enterprises was then computed. Of a market with a supply of 212644 units, a total demand of 2290059 units, a market share of 86% is potentially realizable according to the survey. In the technical study, the operations, inventory systems and scheduling are all computed and taken into account. In addition to that, a facility must be designed and should be able to contain all areas and machines in the manufacturing plant. After discerning the required manpower and machines, an ideal facility layout and location was chosen. In the Financial study, the different costs and revenues were tabulated with the help of different financial statements. Balance sheets, income statements, cash flows are examples of these statements. Also, a number of tests were conducted. Among these tests are the test for liquidity, financial leverage, debt service and operational efficiency. Also computed was the net present value of the company, which amounted to 9 million, thereby, making the company financially feasible. In the Socio-Profitability study, different criteria were selected and values were assigned to the different benefits that HIT Enterprises, Inc. imparts to society. Sensitivity Analysis was also conducted, and the Net Present Value for Socio-Profitability turned out to be 29 million and the IRR was higher than the set value of 20%, making the company socially acceptable and justifiable.